KESULITAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS III SDN 22 SULUR MEDAN KECAMATAN SAMBAS TAHUN PELAJARAN 2023-2024 - Ria Purnama Sari (Lunggi Journal, 2025)
The purpose of this study was to find out about: 1) Types of student learning difficulties during the Indonesian language learning process in class III SDN 22 Sulur Medan, Sambas District, 2023-2024 Academic Year. 2) Internal and external factors of students in Indonesian language learning in class III SDN 22 Sulur Medan, Sambas District, 2023-2024 Academic Year. This study uses a qualitative approach with a phenomenological research type. Data collection techniques in this study use interview, observation, and documentation techniques. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Data validity checking techniques use source triangulation and member check. The results of this study show that class III students are as follows: (1) have difficulty listening, especially in understanding the teacher's explanation due to the influence of the use of everyday regional language. (2) have difficulty speaking, especially when asked to speak in front of the class, students express feelings of nervousness and fear of being laughed at. (3) difficulty reading, especially when encountering foreign words or sentences. (4) difficulty writing, especially when asked to rewrite sentences that the teacher has said but there are students who have difficulty doing so. Furthermore, regarding internal and external factors of learning difficulties in grade III students, namely: (1) family factors, especially related to parental support and guidance in the learning process. (2) school factors, especially related to learning methods and time management. (3) community factors, including the influence of the social environment and activities outside of school.